1996
DOI: 10.1002/(sici)1520-636x(1996)8:1<88::aid-chir15>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoretic enantiomeric separations using the glycopeptide antibiotic, teicoplanin

Abstract: Teicoplanin is the third in a series of macrocyclic glycopeptide antibiotics that has been evaluated as a chiral selector in capillary electrophoresis (CE). It was used to resolve over 100 anionic racemates at low selector concentrations. Like the other related glycopeptide antibiotics, its enantioselectivity tends to be opposite to that of the ansa‐type antibiotics which prefers cationic compounds, particularly amines. Factors that affect teicoplanin‐based enantioseparations include the selector concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…It is clear that modification of teicoplanin by acetonitrile leads to slight improvement of the electrode's enantioselective properties. These results are in good concordance with ones obtained by Rundlett et al [16] and Tesarˇova et al [21] when teicoplaninbased systems were used for capillary electrophoretic and chromatographic separations. These results also prove that both electrodes can be used for R-baclofen enantioanalysis.…”
Section: Selectivity Of the Electrodessupporting
confidence: 91%
See 1 more Smart Citation
“…It is clear that modification of teicoplanin by acetonitrile leads to slight improvement of the electrode's enantioselective properties. These results are in good concordance with ones obtained by Rundlett et al [16] and Tesarˇova et al [21] when teicoplaninbased systems were used for capillary electrophoretic and chromatographic separations. These results also prove that both electrodes can be used for R-baclofen enantioanalysis.…”
Section: Selectivity Of the Electrodessupporting
confidence: 91%
“…Organic modifiers enhance the electrostatic interaction forces required for chiral recognition. Thus, the results of capillary electrophoretic enantiomeric separations performed by Rundlett et al [16] showed that the addition of low concentrations of acetonitrile improves the enantioselective properties of teicoplanin-based systems. Tesarova et al [21] also observed the improvement of teicoplanin's enantioselective properties during high-performance liquid chromatographic and capillary electrophoretic separations of amino acids enantiomers.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the addition of methoxyethanol was substantial in the optimization of the separation conditions with A53312B. 207 The studies [203][204][205][206][207][208] are highly informative and inspirational as far as the enantioselective capabilities of the glycopeptide macrocyclic antibiotics to various compound types are concerned.…”
Section: E Macrocyclic Antibioticsmentioning
confidence: 99%
“…Macrocyclic glycopeptide-based stationary phases were introduced in 1994 [20] and have been used to separate an array of enantiomeric compounds that includes amino acids [21][22][23][24][25][26][27][28][29]. The macrocyclic glycopeptide provides a number of chiral centers, binding pockets, sites of aromaticity, and hydrogen donors/acceptors enabling a variety of interactions such as hydrophobic, hydrogen bonding, dipole, -, steric repulsion, and ionic.…”
Section: Resultsmentioning
confidence: 99%